2015
DOI: 10.1159/000439222
|View full text |Cite
|
Sign up to set email alerts
|

Cytidine Deaminase as a Molecular Predictor of Gemcitabine Response in Patients with Biliary Tract Cancer

Abstract: Objective: Gemcitabine-based chemotherapy is regarded as the standard treatment for biliary tract cancer (BTC). Potential biomarkers for gemcitabine response include the activities of cytidine deaminase (CDA), human equilibrative nucleoside transporter 1 (hENT1), deoxycytidine kinase (DCK), and ribonucleotide reductase M1 (RRM1). Here, we investigated whether single nucleotide polymorphisms (SNPs) in their encoding genes were associated with the efficacy of gemcitabine chemotherapy in treating BTC. Methods: We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…Several genetic and epigenetic alterations, including gene mutations, amplifications, polymorphic status or altered gene/protein expression and activity, have been associated with gemcitabine response and toxicities [ 20 , 25 ]. In our previous retrospective study of patients with advanced BTC who were treated with gemcitabine plus cisplatin, the variant rs1048977 allele in the CDA gene was associated with tumor response in a dominant model [ 14 ]. In the present study, however, none of the tested SNPs was significantly associated with RFS or with hematologic or non-hematologic toxicities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic and epigenetic alterations, including gene mutations, amplifications, polymorphic status or altered gene/protein expression and activity, have been associated with gemcitabine response and toxicities [ 20 , 25 ]. In our previous retrospective study of patients with advanced BTC who were treated with gemcitabine plus cisplatin, the variant rs1048977 allele in the CDA gene was associated with tumor response in a dominant model [ 14 ]. In the present study, however, none of the tested SNPs was significantly associated with RFS or with hematologic or non-hematologic toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…However, these were small-scale or retrospective studies. Our group recently reported that a polymorphism in the gene encoding cytidine deaminase (CDA) may predict the efficacy of gemcitabine-based chemotherapy in patients with advanced BTC [ 14 ]. Deoxycytidine kinase (dCK) is a key enzyme that activates gemcitabine by phosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the relationship between CDA polymorphisms and GCB toxicity are inconsistent (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Severe GCB toxicity in NSCLC patients was reported in cases with heterozygous c.437CT variant and, to a lesser degree, in those with homozygous c.435TT variant (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…2-35 (11-15). Data regarding toxicity related to CDA polymorphisms are inconsistent (16)(17)(18). Nevertheless, several studies demonstrated that single nucleotide polymorphism (SNP) of CDA c.79 A>C, c.208 G>A and c.435C>T, with resulting decreased serum CDA concentration, may lead to severe toxicity induced by GCB (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…96 In vitro, macrophage-induced CDA upregulation in human Panc-1 pancreatic tumor cell line has been shown to confer gemcitabine resistance. 111 Data from ample studies have indicated that CDA polymorphisms alter CDA enzyme activity and the pharmacokinetics of gemcitabine, [135][136][137][138] and three functional polymorphisms of CDA (rs2072671, CDA 79A  C; rs60369023, CDA 208G  A; and rs1048977, CDA 435C  T) could predict the clinical outcomes of gemcitabine-based tumor chemotherapy. 33,135,136 …”
Section: Cdamentioning
confidence: 99%